Let's write the coordinates in consistent order, starting from the right angle and traverse the short side first.
A is (2,3), (4,3), (2,6)
B is (-4, -1), (-2,-1), (-4,-4)
Reflecting A in the x axis negates the y coordinates and keeps the x coordinates the same.
A' is (2,-3), (4,-3), (2,-6)
We want a translation of X=(c,d) that gives A'+X=B so X=B-A', let's work that out for the three points
(-4,-1)-(2,-3)=(-6,2)
(-2,-1)-(4,-3)=(-6,2)
(-4,-4)-(2,-6)=(-6,2)
It's consistent, c=-6, d=2
Answer: c=-6, d=2